Utilização dos espaços alternativos de aprendizagens na escola : possibilidades para a iniciação científica como estratégia para o ensino de biologia - Fares, Munir Kassen (2018)
Classrooms are the most well-known spaces for learning to take place. However, there are other places called alternative spaces, in which learning may also occur. Thus, we must consider that the educational process takes place within the most diversified environments. In this process, the need arises to create parallel to the school, other means and educational environments, not only alternative, but functionally complementary to it. Thinking about students' learning, using alternative spaces, where these spaces favor a better environmentlearning relationship, it was from these looks that my motivation arose to carry out this work, and with it, open the way for a The aim of this work is to point out the various possibilities of using the alternative spaces of learning in the school environment, through scientific initiation. And from this diagnosis, build a systematized proposal for the teaching of Science and Biology.